Science and pseudoscience in social work practice - Thyer, Bruce A.; Pignotti, Monica (Springer Publishing Company, 2015)
"Science is a way of thinking about and investigating the accuracy of assumptions about the world. It is a process for solving problems in which we learn from our mistakes. Social work has a long history of social reform and helping efforts. Let us continue this by paying attention to the important message of this book. --Eileen Gambrill, PhD, School of Social Welfare University of California at Berkeley (From the Foreword) Although many psychosocial interventions used in social work practice have strong research evidence supporting their efficacy, a surprising number do not, potentially resulting in harmful outcomes. In this book, the authors cast a critical eye on the reality of commonly used scientific and pseudoscientific practices in social work today. Stressing the need for separating research-based practices from those not supported by adequate levels of evidence, they examine the scientific and pseudoscientific bases for popular social work interventions used in a variety of treatment settings. The text examines the misuse of legitimate research and describes how social work education training can and should discourage pseudoscience. The concluding chapter describes pathways through which social work practice can become more firmly grounded in contemporary scientific research. This engaging book is intended for courses in critical thinking and evidence-based practice and is a valuable resource for all social work students and practitioners. Key Features: Promotes critical thinking regarding the evidence-based research--or lack thereof--behind a variety of social work interventions Written by renowned social work educators Addresses the history and characteristics of pseudoscience Examines pseudoscience practices in assessment and work with children, adolescents, adults, and individuals with developmental difficulties
Keywords: Social service -- Practice.; Pseudoscience.; Social case work.; Social work education.; Social sciences.; Social service.; Physical sciences.; Sociology.; Social problems.; Prognosis.; Outcome assessment (Medical care); National health services.; Social control.; Diagnosis.; Medical care.; Health services administration.; Quacks and quackery.; Malpractice.; Science.; Social Sciences; Social Work; Natural Science Disciplines; Sociology; Social Problems; Prognosis; Outcome Assessment, Health Care; Health Services; Jurisprudence; Disciplines and Occupations; Social Control, Formal; Health Care Facilities, Manpower, and Services; Outcome and Process Assessment, Health Care; Diagnosis; Quality of Health Care; Health Care Economics and Organizations; Anthropology, Education, Sociology and Social Phenomena; Analytical, Diagnostic and Therapeutic Techniques and Equipment; Delivery of Health Care; Health Care Evaluation Mechanisms; Health Services Administration; Health Care Quality, Access, and Evaluation; Treatment Outcome; Quackery; Malpractice; Science; Patient Care; Service social -- Pratique.; Parasciences.; Service social personnel.; Service social -- Étude et enseignement.; Sciences sociales.; Service social.; Sciences physiques.; Sociologie.; Problèmes sociaux.; Pronostics (Pathologie); Évaluation des résultats (Soins médicaux); Services de santé.; Contrôle social.; Diagnostics.; Prestation de soins.; Services de santé -- Administration.; Charlatanisme.; Responsabilité professionnelle.; Sciences.; Soins médicaux.; Droit.; social sciences.; physical sciences.; sociology.; social issues.; diagnosis.; malpractice.; sciences (philosophy); science (modern discipline); law (discipline); POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Human Services.; Social service; Social sciences; Social problems; Social control; Quacks and quackery; Physical sciences; National health services; Medical care; Health services administration; Pseudoscience; Social case work; Social service -- Practice; Social work education; Electronic books.